Ionic liquid incorporated PVC based polymer electrolytes: electrical and dielectric properties - Siti Khatijah Deraman,; Nor Sabirin Mohamed,; Ri Hanum Yahaya Subban, (Universiti Kebangsaan Malaysia, 2014)
This paper is focussed on conductivity and dielectric properties of Poly (vinyl) chloride (PVC)- ammonium triflate (NH4CF3SO3) - butyltrimethyl ammonium bis (trifluoromethyl sulfonyl) imide (Bu3MeNTf2N) ionic liquid, electrolyte system. The electrolyte is prepared by solution cast technique. In this work, the sample containing 30 wt. % NH4CF3SO3 exhibits the highest room temperature conductivity of 2.50 × 10-7 S cm-1. Ionic liquid is added in various quantities to the 70 wt. % PVC-30 wt. % NH4CF3SO3 composition in order to enhance the conductivity of the sample. The highest conductivity at room temperature is obtained for the sample containing 15 wt. % Bu3MeNTf2N with a value of 1.56 × 10 -4 S cm-1. The effects of ionic liquid addition on the frequency dependent dielectric properties of PVC based electrolytes is investigated by electrochemical impedance spectroscopy (EIS) at room temperature. The values of dielectric constant were found to increase with increasing conductivity of the samples. Analysis of the ac conductivity data showed the electrolytes to be of the non-Debye type.